Rapid cardiac compression: An effective method of avian euthanasia. (18th July 2018) - Engilis, Andrew; Engilis, Irene E.; Paul-Murphy, Joanne
Abstract: Proper methods for euthanasia are critical for research with birds. Training in these methods is generally required by institutional animal care and use committees for any research that involves handling of birds, even if the intent is for birds to be released into the wild. Rapid cardiac compression (RCC) remains a preferred method for quick euthanasia in field settings but has not been described adequately in the literature. We describe proper application of RCC for euthanasia of small birds. We also provide external cues for a bird as it progresses toward death as well as other considerations when using RCC. Note that RCC is also known as "thoracic compression, " but that term is not biologically accurate and should be abandoned.